The Global Self-Reactivity Profile of the Natural Antibody Repertoire Is Largely Independent of Germline DH Sequence - Vale, Andre M.; Cavazzoni, Cecília B.; Nobrega, Alberto; Schroeder, Harry W. (Frontiers in Immunology, 2016)
Natural antibodies (NAbs) are produced in the absence of exogenous antigenic stimulation and circulate in the blood of normal, healthy individuals. These antibodies have been shown to provide one of the first lines of defense against both bacterial and viral pathogens. Conservation of the NAb repertoire reactivity profile is observed both within and across species. One view holds that this conservation of NAb self reactivities reflects the use of germline antibody sequence, whereas the opposing view holds that the self-reactivities reflect selection driven by key conserved self-antigens. In mice, B-1a B cells are a major source of NAbs. A significant fraction of the B-1a antibody repertoire is devoid of N nucleotides in H chain complementarity determining region 3 (CDR-H3) and thus completely germline encoded. To test the role of germline DH sequence on the self-reactivity profile of the NAb repertoire, we examined the composition and self-antigen specificity of NAbs produced by a panel of DH gene targeted BALB/c mice, each strain of which expresses a polyclonal, altered CDR-H3 repertoire that differs from the wild-type norm. We found that in most cases the same key self-antigens were recognized by the NAbs created by each DH altered strain. The differences in reactivity appeared to represent the genetic signature of the NAb repertoire of each mouse strain in of reactivities. These findings suggest that although germline CDR-H3 sequence may facilitate the production of certain NAbs, a core set of self-antigens are likely the main force driving the selection of Nab self-specificities.